Caracterização bioquímica em sementes de uma população natural de Acrocomia aculeata (Jacq.) Lodd. ex Mart - Alcantara, Marcelo Augusto Mendes [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Acrocomia aculeata is a species of large occurrence in the Brazilian Cerrado and is also present in some other biomes that surround it, with great potential for use of all plant components (leaves, stems and fruit). It also covers a range with numerous utilities and can be framed in different areas of study. Within this context, the aim of this study was to characterize the genetic variability in seed a natural population of Acrocomia aculeata through the levels of starch compounds, carbohydrates, lipids and proteins (albumin, globulin, glutelin and prolamin) and macronutrients (nitrogen, phosphorus, potassium, calcium, magnesium and sulfur). They used fruit and seeds originating from Acrocomia plants aculeata collected 30 open pollinated trees in a population located in areas of environmental preservation of the CESP in the old site of HPP works. Eng. Sergio Motta in the municipality of Rosana region - SP in Pontal do Paranapanema. Laboratory tests were carried out in the Laboratory of Genetics of Populations and Forestry, Soil Analysis Laboratory and Tissue Plant and the Agronomic Institute of Campinas. Statistical analysis showed that for the starch content, the species showed overall average of 0.27 mg g-1. For carbohydrates: 10.24 mg g-1. Lipids have an overall average to the value of 20.23 mg g-1. The average levels of proteins found were: Albumins, 16.39 g kg-1, glutelin, 6.69 g kg-1, Prolamins, 21.81 g kg-1, and globulins with 41.82 g kg-1. Analysis of the macronutrient content with values of 23.6 g kg-1, for nitrogen, for calcium 1.53 g kg-1, phosphorus 6,64 g kg-1, potassium 3.33 g kg-1, magnesium 1.80 g kg-1, and sulfur 1.69 g kg-1. The experimental coefficient of variation was maintained at appropriate values for the analyzes with the highest being 24.89% for calcium and 0.89% to lower lipids, indicating good precision the estimates. The indices of heritability and coefficient of variation of the gene patterns showed high value...

Acrocomia aculeata é uma espécie de grande ocorrência no Cerrado brasileiro e está presente também em alguns outros biomas que o circundam, apresentando grande potencial de utilização de todos os componentes da planta (folhas, estipes e fruto). Também abrange um leque com inúmeras utilidades, podendo ser enquadrada em diversas áreas de estudo. Com base nesse contexto, o objetivo deste estudo foi caracterizar a variabilidade genética em sementes de uma população natural de Acrocomia aculeata por meio dos teores dos compostos de amido, carboidratos, lipídios e proteínas (albuminas, globulinas, glutelinas e prolaminas) e dos macronutrientes (nitrogênio, fósforo, potássio, cálcio, magnésio e enxofre). Foram utilizados frutos e sementes originados de plantas de Acrocomia aculeata coletadas de 30 árvores de polinização livre em uma população localizada em áreas de preservação ambiental da CESP no antigo canteiro de obras da UHE. Eng. Sergio Motta, na região do município de Rosana - SP no Pontal do Paranapanema. As análises laboratoriais foram realizadas no Laboratório de Genética de Populações e Silvicultura, Laboratório de Análise de Solo e Tecido Vegetal e do Instituto Agronômico de Campinas. As análises estatísticas mostraram que para os teores de amido, a espécie apresentou média geral de 0,27 mg g-1. Para os carboidratos: 10,24 mg g-1. Os lipídios apresentam uma média geral com o valor de 20,23 mg g-1. Os teores médios de proteínas encontrados foram: Albuminas, 16,39 mg g-1, Glutelinas, 6,69 mg g-1, Prolaminas, 21,81 mg g-1 e globulinas com 41,82 mg g-1. As análises dos teores de macronutrientes apresentaram valores de 23,6 g kg-1 para o nitrogênio, para o cálcio 1,53 g kg-1, fósforo 6,64 g kg-1, o potássio 3,33 g kg-1, o magnésio 1,80 g kg-1 e o enxofre 1,69 g kg-1. O coeficiente de variação experimental se manteve em valores adequados para as análises com o maior sendo 24,89% para...
Keywords: Cerrados; Palmeira; Plantas - Analise